2014
DOI: 10.1126/scisignal.2004993
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal SH3 Domain Contributes to the Intramolecular Inhibition of Vav Family Proteins

Abstract: Vav proteins are phosphorylation-dependent guanine nucleotide exchange factors (GEFs) that catalyze the activation of members of the Rho family of guanosine triphosphatases (GTPases). The current regulatory model holds that the nonphosphorylated, catalytically inactive state of these GEFs is maintained by intramolecular interactions among the amino-terminal domains and the central catalytic core, which block the binding of Vav proteins to GTPases. We showed that this autoinhibition is mechanistically more comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(123 citation statements)
references
References 65 publications
10
111
1
1
Order By: Relevance
“…We focused on RAC1 because mutation of the VAV1 CSH3 domain strongly activates RAC1, whereas its effects on the r GTPases CDC42 and RHOA are more modest. 27 RAC1 also has been shown to be activated by NPM-ALK in ALCL cells, and a Rac small molecule inhibitor blocked lymphoma development and dissemination. 50,51 We showed that cells expressing VAV1-GSS were exquisitely sensitive to azathioprine, which inhibits activation of RAC1 but not of CDC42 or RHOA, 33,34 Other clinically available drugs that inhibit RAC1 and have been proposed to be repurposed as anticancer agents include metformin, statins such as simvastatin, and R-ketorolac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on RAC1 because mutation of the VAV1 CSH3 domain strongly activates RAC1, whereas its effects on the r GTPases CDC42 and RHOA are more modest. 27 RAC1 also has been shown to be activated by NPM-ALK in ALCL cells, and a Rac small molecule inhibitor blocked lymphoma development and dissemination. 50,51 We showed that cells expressing VAV1-GSS were exquisitely sensitive to azathioprine, which inhibits activation of RAC1 but not of CDC42 or RHOA, 33,34 Other clinically available drugs that inhibit RAC1 and have been proposed to be repurposed as anticancer agents include metformin, statins such as simvastatin, and R-ketorolac.…”
Section: Discussionmentioning
confidence: 99%
“…Because the VAV1 CSH3 domain mediates autoinhibition of VAV1 GEF activity, 27 we hypothesized that VAV1 fusions, which lack this domain, promote VAV1 activation. Because VAV1 mediates cytoskeletal remodeling, 28 we first performed immunofluorescence for actin in adherent NIH-3T3 fibroblasts transfected with VAV1-GSS, wild-type (wt)VAV1, or an empty control vector.…”
Section: Vav1-gss Promotes Cell Migration and Growthmentioning
confidence: 99%
“…To this end, we used standard genomic recombination techniques to insert an ectopic cassette containing a cDNA fragment encoding a truncated, hemagglutinin (HA)-tagged Vav2 ⌬1-184 mutant protein (here termed OncoVav2) downstream of the first exon of the mouse Vav2 locus. We have shown before that this type of truncated Vav protein shows phosphorylation-independent, constitutive exchange activity due to the removal of the N-terminal inhibitory domains (14,(27)(28)(29). To make possible the inducible expression of this protein, this cassette contained 5=-located Stop-Neo R DNA sequences flanked by loxP sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sin embargo, su fosforilación tras la estimulación celular hace que estas interacciones intramoleculares se rompan y las proteínas Vav adquieran una conformación "abierta" plenamente activa [3]. Los dominios estructurales y sitios de fosforilación implicados en este proceso han sido descubiertos recientemente [4,5]. Hay que destacar que estas proteínas ejercen pluriempleo a nivel celular, puesto que pueden estimular vías de señalización alternativas independientemente de su actividad enzimática (Figura 1).…”
Section: Discussionunclassified